Taphonomy and Paleoecology of Fossil Insect Assemblages from Old Crow River (CRH-15) Northern Yukon Territory, Canada - Morlan, Richard; Matthews, John (Géographie physique et Quaternaire, 1983)
ABSTRACTThe paleoenvironmental message delivered by any fossil assemblage is nearly always filtered to some degree by taphonomic and preservational biases. This paper discusses some of the types of biases that affect the composition of fossil Coleoptera (beetles) assemblages. Eight samples from a single site in the northern Yukon provide the raw data for the analysis. They represent different types of host sediments — ranging from autochthonous peats to organic rich alluvial sands. For each assemblage the authors noted the state of preservation of the fossils, counted the individual anatomical parts (pronota, heads, elytra) referred to each taxon and the number of articulated or partially articulated specimens, and sorted the fossils on the basis of predefined ecological groups. The resulting data were then examined statistically, and compared with paleoenvironmental conclusions derived by examination of the present distribution of the taxa in each assemblage. The content of the insect assemblages varies with the type of host sediment. Insect fossils from autochthonous sediments deliver a reliable local environmental signal. Allochthonous sediments, such as alluvium, might be expected to contain fossils that provide an integrated picture of the regional environment, but in the Yukon such samples are seriously overrep resented by Lepidophorus lineaticollis, a weevil that lives on or near sandy floodplains. Deviations in the representation of particular anatomical elements of L. lineaticollis from one sample to another warn of other more subtle taphonomic biases that may also skew the content of northern fossil insect assemblages.